Strategic role of international cooperation in the generation of resources for the integral development of the region Huánuco - Ramírez Tabraj, Eudosio (2009)
A study was conducted in order to promote the rational use of resources and adequate financial and international cooperation to achieve comprehensive development in the region for which information was gathered on the authorities cooperating in the process development and growth of this part of the country through the transfer of financial resources and the actual implementation of public investment projects, whose implementation has generated needs of the target population, but is in full, at least in partly because the needs generated other needs.